(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid advancement of science and technology has led to significant transformations in higher education, particularly in medical and biological sciences. Microbiology, as a fundamental subject in medical education, requires students to develop analytical thinking, problem-solving, and research competencies. This article presents a methodological model for integrating STEM (Science, Technology, Engineering, Mathematics) components into the teaching of microbiology to enhance students’ analytical skills. The research highlights the theoretical foundations, pedagogical approaches, and practical tools that contribute to developing analytical competence among students. Experimental results demonstrate the effectiveness of STEM-based teaching in improving students’ engagement, cognitive activity, and analytical reasoning in microbiological problem-solving.